Glycerol-3-phosphate acyltransferases and metabolic syndrome: recent advances and future perspectives - Huang, Yinqiong; Hu, Keyue; Lin, Shu; Lin, Xiahong (Expert reviews in molecular medicine, 2022)
Triglycerol-3-phosphate acyltransferases (GPATs) are the key enzymes in the first step of the synthesis of triacylglycerol (TAG). In mammals, there are four isoforms of GPATs. GPAT1 and GPAT2 are localised in the outer mitochondrial membrane, while GPAT3 and GPAT4 are localised in the endoplasmic reticulum. Previous research has emphasised that GPAT plays a critical effect on the development of metabolic syndromes, such as liver steatosis, obesity, and insulin resistance. In this review, we will critically evaluate the regulatory effects of GPATs isoforms in metabolic syndrome. In addition, we also discuss perspectives on clinical intervention strategies for the neurometabolic disease.